Disinfection by UV - Chai, Isaiah Nehemiah (Nanyang Technological University, 2021)
The unprecedented COVID-19 global pandemic has caused pandemonium worldwide. As of today, the death toll has exceeded approximately 3 million globally. Besides mask wearing and safe distancing measures, various disinfection techniques have also been widely applied to reduce the spread of the virus in key industries such as healthcare and food. In the food industry, infected asymptomatic patients may spread the virus through cough droplets when they handle food packaging in markets. To address this problem, disinfection methods via UV emission to render the virus harmless have been sold in the market. However, the efficacy of the method may vary from one supplier to another as it depends on several factors such as UV intensity, distance, and duration of disinfection etc. Hence, this project evaluated the efficacy of several UVC LEDs available in the market and investigated the effect of UV wavelength, intensity, distance, and duration of UVC exposure as well as bacteria growth stage disinfection performance on food plastic packaging. Due to safety protocol, the E.Coli K12-MG1655 strain was selected and used as the model organism for this disinfection study. With respect to distances studied (3, 6, 9 and 12 cm), the experimental data showed that a vertical height at 3 cm is the most effective in inactivating bacteria while UV LED with wavelength of 254 nm is the most effective in inactivating bacteria, followed by 260 nm and finally, 270 nm. The study also found that disinfection can be carried out effectively when the bacteria is in the exponential growth phase. Furthermore, SEM analysis revealed negligible damage to the plastic packaging after exposure to UV radiation within a 30 minutes duration. Hence, it can be concluded that shortest distance and lower UVC wavelength are the most optimal parameters in inactivating organisms without damaging the plastic packaging material.